Identifikasi dan Evaluasi Risiko Kegagalan Kualitas Crude Palm Oil dengan Metode FMEA: Studi Kasus di PKS Tanjung Seumatoh - Nurmalawati; Pramanda Ryan; Dewiyana; Rahmansyah (Universitas Katolik Darma Cendika, 2024)
This study aims to analyze the factors influencing the quality of Crude Palm Oil (CPO) at the Tanjung Seumatoh Palm Oil Mill (PKS) using the Failure Mode and Effect Analysis (FMEA) method. FMEA was employed to identify and evaluate potential failure risks that could cause the CPO quality to fall outside the company’s established standards. Based on the Risk Priority Number (RPN) calculations, the factor with the highest RPN was machine (RPN = 180), followed by raw material and work method, both with an RPN of 144. Other factors, such as environment, operator, and maintenance, did not show significant RPN values (below 120). The results indicate that poorly maintained machinery, suboptimal raw materials, and non-standard work methods are the primary causes of reduced CPO quality. To improve CPO quality, it is recommended that the company perform regular machine maintenance and modernization, ensure optimal raw material maturity through strict sorting, and enhance training and supervision of work methods. Implementing these corrective measures is expected to improve product quality and reduce the risk of failures in the production process.